Comparison of glomerular filtration rate estimated by plasma clearance method with modification of diet in renal disease prediction equation and Gates method - Prasad, N. (Medknow Publications & Media Pvt Ltd, 2012)
Glomerular filtration rate (GFR) prediction equations are widely used in clinical practice for quick assessment of kidney function. Gates method using radionuclide technique is an alternative to prediction equations for quick assessment of GFR. Aim of the study was to compare Gates method and modification of diet in renal disease (MDRD) equation in a sizeable patient population with wide range of renal function to evaluate their clinical utility. GFR was estimated in 897 subjects with wide range of renal function by gates method, and MDRD equation and results were compared against measured GFR. Subjects were divided in to 4 groups (0-30 ml, 31-60 ml, 61-90 ml, >90 ml) on the basis of measured GFR and comparison between two methods done through linear regression analysis. Analysis of R(2) indicated that 56% of the interindividual variability for Gates GFR was in accordance to variation in measured GFR, in the GFR range of (0-30 ml), this value dropped to 39% in the GFR range of 31-60 ml, 40% in the GFR range of 61-90 ml, 26.4% in the GFR range of >90 ml, the corresponding figure for MDRD GFR were 47.9%, 31.1%, 17.6% and 16.1%, respectively. Gates method is more precise for GFR estimation at all levels of renal function.